(untitled) (Psychology Travelogs, 2022)
The phenomenon of "professional burnout" syndrome is an integral part of the professional activity of police officers, who in their professional activities are constantly under the pressure of a risk factor, are forced to perform tasks in conditions of insufficient information, lack of time, high responsibility for the results of their activities, and also demonstrate communicative competence and communicate intensively with other people. The professional activity of employees of the National Police of Ukraine is usually carried out under the influence of special psychological, social and legal conditions. The adverse effect of the characteristics of professional activity on the personality of a police officer can lead to the phenomenon of "burnout", both professional and emotional, as a result of which professional motivation is gradually lost, neurotic reactions, mental functional disorders and various somatic diseases appear. Daily emotional stress potentially carries the danger of severe experiences related to professional activity, which is why the syndrome of "professional burnout" arises as a result of the accumulation of negative emotions, which, in turn, leads to emotional exhaustion of police officers.